A dependência econômica do Brasil em Caio Prado Júnior: uma análise das obras da década de 1950 - Tauil, Carlos Eduardo [UNIFESP] (2015)
The work being presented has the goal of recapturing Caio Prado Jr.?s thoughts and analytical categories to debate the Brazilian Economical Dependency, his main book, ?Formação do Brasil Contemporâneo?, published in 1942 was part of the country?s development ? from the arrival of the Portuguese ? in the general evolution of the European mercantilism and capitalism. In this instance, Caio Prado Jr. attributed a sense of colonization imbued throughout Brazilian history. However, after World War I and, more specifically after World War II, Brazil was inserted into a new international economical context. The debate about the position which the country occupied in this new world order had its apex in the 1950s with published texts by developmentalists, such as Raul Prebisch and Celso Furtado, little was taken into consideration from Caio Prado Jr.?s analysis. Therefore, we understand that the return of the Marxist author?s reflections about how Brazil developed after the armistice, can bring us new conceptions about the role that the country had in international economy, which were the pieces of the Brazilian economic policy in the 1950s, as well as a new perspective to the sense of colonization.